Menguji Pengaruh Rasio Keuangan Perusahaan Terhadap Financial Distress - Diah Nurdiwaty; Badrus Zaman (Jurnal Penelitian Teori & Terapan Akuntansi (PETA), 2021)
Investors who want to invest, or creditors who will provide loans, will be vigilant and ascertain whether the company is experiencing financial difficulties or the company is in good condition. Therefore, it is necessary to analyze the company's financial statements by looking at their financial ratios.This study aims to examine the effect of independent variables in the form of Liquidity Ratios, Solvency Ratios and Profitability Ratios on Financial Distress as the dependent variable. This research was conducted on manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange in 2013-2016 with a total population of 42 companies. The sampling technique in this study used purposive sampling which resulted in 14 samples in a period of 4 (four) years, namely 56 samples. The analytical method used in this study is logistic regression analysis which is processed using SPSS 23.The results of this study indicate that simultaneously the Liquidity Ratio, Solvency Ratio, and Profitability Ratio have a significant effect on financial distress. Partially, the variables of Liquidity Ratio, Solvency Ratio, and Profitability Ratio have no significant effect on financial distress.